Antidepressant induced cholestasis: hepatocellular redistribution of multidrug resistant protein (MRP2). Issue 2 (1st February 2003) - Milkiewicz, P; Chilton, A P; Hubscher, S G; Elias, E
Abstract : Background: We report two cases of antidepressant induced cholestasis. Case reports: We describe the first reported case of acute cholestasis due to citalopram (selective serotonin reuptake inhibitor) occurring in a patient who also experienced obstetric cholestasis in association with each of three pregnancies; in a second patient cholestasis developed due to dothiepin (tricyclic antidepressant), and six years later due to paroxetine. In both cases liver biopsies showed features of a "pure" cholestasis with total resolution within 1–6 months after withdrawal of the causative drug. Immunostaining for the canalicular transporter, multidrug resistant protein 2 (MRP2), responsible for biliary secretion of several organic anions including bilirubin glucuronides, showed sustained expression in both biopsies as well as relocalisation with appearance of strong staining of the basolateral membrane of the hepatocyte. This finding has also not been reported previously. Conclusions: We postulate that intracellular redistribution of MRP2 may reflect an adaptive compensatory mechanism which helps in the elimination of the drug or its cholestatic metabolites from the hepatocyte back to the sinusoidal space and subsequent excretion in urine. Changes seen in these two patients differ from findings previously reported in rats where downregulation of mrp2 occurs in response to experimentally induced cholestasis. We speculate that the rat is more advanced than humans in its ability to downregulate canalicular transporter expression as protection against progressive intrahepatic cholestasis.